Innovative Governance Dalam Penyelengggaraan Pemerintahan Desa Di Kabupaten Kuantan Singingi (Studi pada Penerapan Aplikasi dan Website Gigades.id) - Febri Eka Sari; Febri Yuliani; Hasim As'ari (Dinasti Review Publisher, 2024)
This research is motivated by the gap in technology, information and communication between villages and cities which causes slow governance in villages. This condition is a challenge for villages to actively participate in the current era of digitalization. The aim of village innovation is to encourage village development of higher quality, effectiveness and efficiency through various activities in village government administration that are more innovative and sensitive to the needs of village communities. This effort can encourage productivity and economic growth in rural communities in a sustainable manner to improve the socio-economic welfare of the community and village independence. However, in the development of village innovation, it has not proceeded according to the plans that have been set. This is because the community's digital awareness is still low, as well as the culture and organizational arrangements of the village government which are not yet fully ready to implement digitalization in the administration of village government. This research aims to analyze and explain innovative governance in the implementation of village government in Kuantan Singingi Regency, as well as identifying obstacles to implementing innovation in the form of the Gigades.id application and website. This research uses the Innovative Governance theory of Sangkala Tahun (2014) which explains that there are 6 criteria for best practices in an innovation, namely impact, partnership, sustainability, leadership and community empowerment, gender equality and social exclusion, innovation in the local context and transferability. This research uses an explanatory qualitative research method with a case study approach that uses data collection techniques through interviews, observation and documentation. The results of this research show that the implementation of village government in Kuantan Singingi Regency has made a breakthrough in the form of innovative governance in the implementation of village government in the form of innovation in the form of the Gigades.id application and website, but it has not been successfully implemented properly by the village government. Findings in the field show that the implementation of partnerships is still formed between the village government and the private sector, the trilogy of good governance in building partnerships has not been implemented well, even though the community has a big role in realizing the implementation of village government. Then the obstacles experienced by this innovation are the lack of socialization carried out by the village government and the private sector to village communities, the low quality of knowledge and innovation skills of village government officials, the inadequate quality of the internet network, and a community culture that is difficult to change.